2014
DOI: 10.1111/1471-0528.12659
|View full text |Cite
|
Sign up to set email alerts
|

Advanced maternal age and pregnancy outcomes: a multicountry assessment

Abstract: Objective To assess the association between advanced maternal age (AMA) and adverse pregnancy outcomes.Design Secondary analysis of the facility-based, cross-sectional data of the WHO Multicountry Survey on Maternal and Newborn Health.Settings A total of 359 health facilities in 29 countries in Africa, Asia, Latin America, and the Middle East.Sample A total of 308 149 singleton pregnant women admitted to the participating health facilities.Methods We estimated the prevalence of pregnant women with advanced age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
255
6
22

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(324 citation statements)
references
References 18 publications
26
255
6
22
Order By: Relevance
“…Criteria for definition of life-threatening conditions, namely gestational age less than 32 weeks, birth weight less than 1,500g, or five-minute Apgar score less than seven (pragmatic criteria for definition of near miss 9 ), correspond to adverse perinatal outcomes and are associated with sociodemographic variables 13 reproductive history, risk behavior 1,18 , and prenatal, delivery, and neonatal care 2,9,19 . Our results corroborated previous studies on factors associated with adverse neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Criteria for definition of life-threatening conditions, namely gestational age less than 32 weeks, birth weight less than 1,500g, or five-minute Apgar score less than seven (pragmatic criteria for definition of near miss 9 ), correspond to adverse perinatal outcomes and are associated with sociodemographic variables 13 reproductive history, risk behavior 1,18 , and prenatal, delivery, and neonatal care 2,9,19 . Our results corroborated previous studies on factors associated with adverse neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Infants born to older mothers showed a nearly twofold risk of neonatal near miss, compared to mothers aged 20 to 34. In the World Health Organization multi-country survey on maternal and newborn health 13 , advanced maternal age was also associated with adverse outcomes such as gestational age less than 37 weeks, birth weight less than 2,500g, and five-minute Apgar less than seven. These characteristics are similar, although more sensitive (higher cutoff points for gestational age and birth weight) than those adopted as pragmatic criteria for the definition of near miss in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…As well as the risks of ovarian stimulation and oocyte collection, studies are consistent as to the increase in perinatal (pre-eclampsia, maternal hypertension, preterm labour, perinatal mortality) and maternal risks (operative delivery and maternal morbidity and mortality) with advanced maternal age at delivery (50 years and 3 months in this case [15][16][17][18]). Specifically assessing the more extremes of maternal age, Laopaiboon et al [15] demonstrated adjusted odds ratios of 3.7 for a severe maternal adverse outcome (defined as a maternal death or a maternal near-miss up to 7 days after giving birth) and 1.6, 1.9 and 2.1 for a low Apgar score at delivery, perinatal mortality and stillbirth in women 45 or over at delivery.…”
Section: Discussionmentioning
confidence: 67%
“…Specifically assessing the more extremes of maternal age, Laopaiboon et al [15] demonstrated adjusted odds ratios of 3.7 for a severe maternal adverse outcome (defined as a maternal death or a maternal near-miss up to 7 days after giving birth) and 1.6, 1.9 and 2.1 for a low Apgar score at delivery, perinatal mortality and stillbirth in women 45 or over at delivery. Schimmel et al [16] demonstrated a significant increase in maternal hypertension (7.3 vs. 4.7 %), maternal diabetes (11.7 vs. 1.2 %), emergency operative delivery (0.9 vs. 0.3 %) and preterm delivery (5.2 vs. 4.0 %) in those between 43 and 47 compared to those 24-27.…”
Section: Discussionmentioning
confidence: 99%
“…Eskiden, 40 yaş ve üzeri kadınlar pek çok plansız çocuğa sahip olmaya meyilli iken, bugün ileri yaşlarda ilk doğum yapan kadınların oranı artmaktadır. İleri anne yaşı maternal ve perinatal risklerde artışa neden olmaktadır (5,6) .…”
Section: Discussionunclassified